Pengaruh Allocentris dan Animosity Terhadap Niat Beli Konsumen Pada Produk Makanan Lokal dengan Ethnocentrism Sebagai Intervening Variabel: The Effect of Allocentrism and Animosity on Consumer Purchase Intention Towards Local Foods Products with Ethnocentrism as Intervening Variable - Riptiono, Sulis (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
The purpose of this study was to investigate the effects of consumer allocentrism towards family, allocentrism towards friends and consumer animosity toward consumer intention to purchase halal products with consumer ethnocentrism as intervening variable. Primary data were collected from 100 students in Kebumen using closed questions with questionnaires. Data were analyzed with spss for windows version 24.0. Path-analyzes was used to test relationship between variables. Based on the results, the study showed that from seven hypothesis proposed, six hypothesis are accepted and only one hypothesis is rejected. The results showed that consumer purchase intentions on local food products are influenced by variable allocentrism to family, allocentrism toward friends, and customer ethnocentrism, while animosity does not have a significant influence toward consumers purchase intention on local food products. Keywords: allocentrism, animosity, ethnocentrism, purchase intention, local product food